(untitled) (Journal of Informatics Education and Research, 2025)
The NDA government has made substantial alterations to the Taxation laws of India. This chapter will analyse the changes in the Indian economy and tax compliance after demonetization, with a specific focus on tactics implemented to address the issue of black money in India. The research will thoroughly investigate the impact of tax compliance and evasion, as well as the legal transparency that emerged throughout this significant transition. The authors will conduct a comparative study of before and post-demonetization tax compliance patterns and evaluate the effectiveness of its implementation. An extensive examination will be conducted to analyse socio-economic issues, technical improvements, legislative changes, and the introduction of new policies through the perspective of digitalization to enhance tax compliance in the nation. The study intends to offer significant insights into the Indian economy, specifically focusing on the implementation of demonetization and its influence on tax compliance and the prevalence of illicit money in India.